Effect of Motivational Enhancement Therapy on Patterns of Substance Abuse in Postpartum Women: A Randomized Clinical Trial - Fatemeh Esmaeilinejad Hasaroeih; Nasim Shahrahmani; Atefeh Ahmadi; Moghaddameh Mirzaee; Katayoun Alidousti; Morteza Hashemian (Guilan University of Medical Sciences, 2022)
Introduction: As a biopsychosocial phenomenon, substance abuse is a major public health problem with negative economic, social, and cultural consequences. Objective: This study aims to determine the effect of Motivational-Enhancement Therapy (MET) on substance abuse patterns in postpartum women with Substance Use Disorder (SUD). Materials and Methods: This clinical trial was conducted on 60 eligible postpartum women with SUD (30 in the intervention group and 30 control), who were selected using a random sampling method from the postpartum unit of a hospital in Kerman, Iran in 2019. The participants in the intervention group attended four individual MET sessions and received four telephone follow-ups. All participants completed a researcher-made substance use pattern checklist before and after the intervention. Data analysis was carried out using McNemar's test, paired t-test, independent t-test, Fisher's exact test, and chi-square test. A P<0.05 was considered statistically significant. Results: The mean age of women was 29.25±5.89 years, and most of them were housewives with elementary education. A significant reduction was observed in the number of opium (P=0.008) and methadone (P=0.003) users after the intervention. Moreover, there was a significant difference in the amount of opium and methadone use (P<0.05). However, no significant difference was found between the two groups in the method and frequency of substance use before and after the intervention. Conclusion: MET is effective in the type and amount of opium and methadone used in postpartum women with SUD. Therefore, it can be used along with other treatments for the treatment of SUD in women after delivery.